2017
DOI: 10.1080/1745039x.2017.1283824
|View full text |Cite
|
Sign up to set email alerts
|

Effects ofLactobacillus caseiandEnterococcus faecalison growth performance, immune function and gut microbiota of suckling piglets

Abstract: This study was carried out to investigate the effects of orally administrated Lactobacillus casei and Enterococcus faecalis on performance, immune function and gut microbiota of suckling piglets. Neonatal piglets (n = 120) were randomly assigned to 4 groups, with 30 suckling piglets in each group. The piglets were from 15 litters, one male and one female piglet were selected for each group in each litter. The Control group was administrated with normal saline, the other groups with L. casei or E. faecalis or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 36 publications
4
26
0
1
Order By: Relevance
“…These findings are supported by earlier studies that showed positive effects on feed intake and growth performance in piglets fed diets supplemented with a complex of lactic acid bacteria during a 21-day post-weaning period [18]. The enhanced growth performance observed in our study is consistent with previous published reports [9,19,20].…”
Section: Discussionsupporting
confidence: 93%
“…These findings are supported by earlier studies that showed positive effects on feed intake and growth performance in piglets fed diets supplemented with a complex of lactic acid bacteria during a 21-day post-weaning period [18]. The enhanced growth performance observed in our study is consistent with previous published reports [9,19,20].…”
Section: Discussionsupporting
confidence: 93%
“…The gastrointestinal tract supplies the largest number of immune cells; therefore, any factors that modify the gut situation will influence immunity (Altmeyer et al, 2014). It was reported that supplementation with L. casei and Enterococcus faecalis in sucking piglets increased serum IgA and IgG, but no treatment effects were observed for IgM (Liu et al, 2017). In our results, the function of growth-retarded calves greatly improved, and GH/IGF-1 was increased after intervention, but serum immunoglobulins demonstrated no obvious changes ( P > 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…The B‐cell isotype switch to IgA production is controlled by transforming growth factor (TGF)‐β; therefore, it is possible that L. casei strain Shirota induce the production of IgA1 and IgA2 via TGF‐β induction . Further, intake of combined probiotics comprising L. casei and Enterococcus faecalis significantly increased the expression level of TGF‐β in the piglet jejunum in another study . In the present study, it can be speculated that the intake of yogurt fermented with L. bulgaricus OLL1073R‐1 may also activate the gut mucosal immune system and increase the expression levels of cytokines in the gut.…”
Section: Discussionmentioning
confidence: 52%
“…27 Further, intake of combined probiotics comprising L. casei and Enterococcus faecalis significantly increased the expression level of TGFβ in the piglet jejunum in another study. 28 In the present study, it can be speculated that the intake of yogurt fermented with L. bulgaricus OLL1073R-1 may also activate the gut mucosal immune system and increase the expression levels of cytokines in the gut. As a result, the salivary IgA secretion might be accelerated by the increase of IgA + B cells mediated via cytokines in the gut.…”
Section: Effects On Mucous Immunity By Intake Of Yogurt Fermented Wmentioning
confidence: 61%